1991
DOI: 10.1095/biolreprod44.6.1113
|View full text |Cite
|
Sign up to set email alerts
|

Role of Epithelial Cells of the Male Excurrent Duct System of the Rat in the Endocytosis or Secretion of Sulfated Glycoprotein-2 (Clusterin)1

Abstract: The localization of sulfated glycoprotein-2 (clusterin; SGP-2) was investigated in the rete testis, efferent ducts, and epididymis of the rat using light (LM) and electron (EM) microscope immunocytochemistry. At the LM level, the epithelial cells of the rete testis and efferent ducts demonstrated an intense immunoperoxidase reaction over their apical and supranuclear regions, and sperm in the lumen of the efferent ducts were unreactive. In the EM, gold particles were found exclusively over the endocytic appara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
155
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(180 citation statements)
references
References 0 publications
23
155
1
1
Order By: Relevance
“…It dissociates from the spermatozoa when they reach the rete testis and the efferent ductules, and is finally endocytosed by the epithelial cells of these ductules (Hermo et al, 1991b;Igdoura et al, 1994). It is demonstrated that SGP-2 is located within the compartments involved in the endocytotic pathways of the nonciliated cells (Hermo et al, 1991b). Therefore it seems to be an appropriate marker for endocytosis in the efferent ductules.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…It dissociates from the spermatozoa when they reach the rete testis and the efferent ductules, and is finally endocytosed by the epithelial cells of these ductules (Hermo et al, 1991b;Igdoura et al, 1994). It is demonstrated that SGP-2 is located within the compartments involved in the endocytotic pathways of the nonciliated cells (Hermo et al, 1991b). Therefore it seems to be an appropriate marker for endocytosis in the efferent ductules.…”
mentioning
confidence: 97%
“…Three major pathways have been reported for the epithelium to reabsorb the fluid. First, the nonciliated cells have a well-developed endocytotic apparatus in the apical cytoplasm such as invaginations of the apical membrane, vesicles, endosomes, multivesicular bodies and lysosomes (Hermo and Morales, 1984;Jones and Jurd, 1987;Hermo et al, 1988Hermo et al, , 1991bRobaire and Hermo, 1988). Studies using electron dense tracers confirmed that these organelles are involved in endocytosis (Hermo and Morales, 1984;Veeramachaneni and Amann, 1991;.…”
mentioning
confidence: 99%
“…Immunohistochemical analysis showed that clusterin was present in spermatogenic cells besides Sertoli cells in the lumen of seminiferous tubules. As mentioned in the introduction, clusterin derived from Sertoli cells bound to the surface of testicular spermatozoa in the rete testis fluid and would be replaced by clusterin from the epididymis or seminal vesicle during sperm migration [3,8,9,32]. Therefore the clusterin observed by us in the inner membrane of normal spermatozoa may have been synthesized by the spermatogenic cells.…”
Section: Discussionmentioning
confidence: 71%
“…Most previous studies have shown that clusterin is secreted into semen by the epididymis and seminal vesicle, and mainly adheres to the surfaces of abnormal spermatozoa [3,8,9,25,32]. Only a few researchers observed clusterin in normal human spermatozoa [2,26,35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation